2020
DOI: 10.1111/1348-0421.12766
|View full text |Cite
|
Sign up to set email alerts
|

In vitro vRNA–vRNA interactions in the H1N1 influenza A virus genome

Abstract: The genome of influenza A virus consists of eight‐segmented, single‐stranded, negative‐sense viral RNAs (vRNAs). Each vRNA contains a central coding region that is flanked by noncoding regions. It has been shown that upon virion formation, the eight vRNAs are selectively packaged into progeny virions through segment‐specific packaging signals that are located in both the terminal coding regions and adjacent noncoding regions of each vRNA. Although recent studies using next‐generation sequencing suggest that mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…In both human H3N2 and avian H5N2 viruses, all eight vRNAs interact with one or more vRNAs and form single networks of intersegment associations (Fournier et al 2012a(Fournier et al , 2012bGavazzi et al 2013aGavazzi et al , 2013b. Similar findings have been reported for human H1N1 virus, in which each vRNA interacts with at least one vRNA through terminal coding regions in many cases (Miyamoto and Noda 2020). Curiously, the networks of intersegment interactions are different among these three strains, and only a few combinations are conserved.…”
Section: Evidence For Direct Vrna-vrna Associationssupporting
confidence: 68%
“…In both human H3N2 and avian H5N2 viruses, all eight vRNAs interact with one or more vRNAs and form single networks of intersegment associations (Fournier et al 2012a(Fournier et al , 2012bGavazzi et al 2013aGavazzi et al , 2013b. Similar findings have been reported for human H1N1 virus, in which each vRNA interacts with at least one vRNA through terminal coding regions in many cases (Miyamoto and Noda 2020). Curiously, the networks of intersegment interactions are different among these three strains, and only a few combinations are conserved.…”
Section: Evidence For Direct Vrna-vrna Associationssupporting
confidence: 68%
“…It has been found that the segmented IAV genome is assembled and packed in viral particles by the action of coordinated packaging sequences and specific amino acids in NP. It has also been previously shown that the packaging of genome segments is strictly dependent on sequences close to the 5 and 3 termini [15,17,36,38,52,53]. The experiments were performed involving constructs with vRNA terminal sequences and reporter genes in the coding regions.…”
Section: Rna Interactionsmentioning
confidence: 99%
“…Genetic reassortment is intimately linked to the copackaging of the eight different IAV genomic segments via cis -acting packaging signals present on each vRNA. These signals, accountable for direct vRNA–vRNA interactions, display segment and subtype specificity and have been mapped throughout the entire length of the vRNAs ( 9 19 ). Hence, the current model for vRNA packaging, which also relies on structural ( 20 ) and genetic data ( 21 25 ), is that vRNA–vRNA interactions between adjacent packaging signals control the bundling of the eight viral segments and their copackaging into virions with a conserved “7 + 1” pattern, with one central segment surrounded by seven others ( 16 , 26 , 27 ).…”
mentioning
confidence: 99%